Emergence of an exotic strain of serotype O foot‐and‐mouth disease virus O/ME‐SA/Ind‐2001d in South‐East Asia in 2015. Issue 1 (30th August 2017) - Qiu, Y.; Abila, R.; Rodtian, P.; King, D. P.; Knowles, N. J.; Ngo, L. T.; Le, V. T.; Khounsy, S.; Bounma, P.; Lwin, S.; Verin, B. C.; Widders, P.
Summary: The O/Middle East‐South Asia (ME‐SA)/Ind‐2001 lineage of foot‐and‐mouth disease virus (FMDV) is endemic in the Indian subcontinent and has been reported in the Middle East and North Africa, but it had not been detected in South‐East Asia (SEA) before 2015. This study reports the recent incursions of this viral lineage into SEA, which caused outbreaks in Vientiane Capital of Lao People's Democratic Republic (PDR) in April 2015, in Dak Nong, Dak Lak and Ninh Thuan Provinces of Vietnam from May to October 2015, and in Rakhine State of Myanmar in October 2015. Disease investigations were conducted during the outbreaks and followed up after laboratory results confirmed the involvement of FMDV O/ME‐SA/Ind‐2001 sublineage d (O/ME‐SA/Ind‐2001d). Affected host species included cattle, buffalo and pig, and all the outbreaks resolved within 2 months. Animals with clinical signs were separated, and affected premises were disinfected. However, strict movement restrictions were not enforced, and emergency vaccinations were only implemented in Vientiane Capital of Lao PDR and Dak Nong and Ninh Thuan Provinces of Vietnam. Clinical samples were collected from each outbreak and examined by nucleotide sequencing of the FMDV viral protein 1 coding region. Sequence analysis revealed that the O/ME‐SA/Ind‐2001d isolates from Lao PDR and Vietnam were closely related to each other and similar to viruses previously circulating in India in 2013. Viruses collected from Myanmar were divergent from viruses of the same sublineage recovered from Lao PDR and Vietnam but were closely related to viruses present in Bangladesh in 2015. These findings imply that at least two independent introductions of O/ME‐SA/Ind‐2001d into SEA have occurred. Our study highlights the transboundary nature of foot‐and‐mouth disease (FMD) and reinforces the importance of improved FMD surveillance and promotion of safer cross‐border trade in SEA to control the risk of introduction and spread of exotic FMDV strains.